A case‐control study to assess the impact of mammographic density on breast cancer risk in women aged 40–49 at intermediate familial risk. Issue 10 (22nd November 2014) - Assi, Valentina; Massat, Nathalie J.; Thomas, Susan; MacKay, James; Warwick, Jane; Kataoka, Masako; Warsi, Iqbal; Brentnall, Adam; Warren, Ruth; Duffy, Stephen W.
<x xml:space="preserve">Abstract</x> Mammographic density is a strong risk factor for breast cancer, but its potential application in risk management is not clear, partly due to uncertainties about its interaction with other breast cancer risk factors. We aimed to quantify the impact of mammographic density on breast cancer risk in women aged 40–49 at intermediate familial risk of breast cancer (average lifetime risk of 23%), in particular in premenopausal women, and to investigate its relationship with other breast cancer risk factors in this population. We present the results from a case‐control study nested with the FH01 cohort study of 6, 710 women mostly aged 40–49 at intermediate familial risk of breast cancer. One hundred and three cases of breast cancer were age‐matched to one or two controls. Density was measured by semiautomated interactive thresholding. Absolute density, but not percent density, was a significant risk factor for breast cancer in this population after adjusting for area of nondense tissue (OR per 10 cm2 = 1.07, 95% CI 1.00–1.15, p = 0.04). The effect was stronger in premenopausal women, who made up the majority of the study population. Absolute density remained a significant predictor of breast cancer risk after adjusting for age at menarche, age at first live birth, parity, past or present hormone replacement therapy, and the Tyrer‐Cuzick 10‐year relative risk estimate of breast cancer. Absolute density can improve breast cancer risk stratification and delineation of high‐risk groups alongside the Tyrer‐Cuzick 10‐year relative risk estimate.